Urban organic community gardening to promote environmental sustainability practices and increase fruit, vegetables and organic food consumption - Paulo Nova; Elisabete Pinto; Benedita Chaves; Margarida Silva (Elsevier, 2020)
Objective: To describe the environmental practices of participants in an urban organic community garden at the beginning of their gardening experience and after a period of six months, and to discover their opinion about how this activity influenced the consumption of vegetables, fruits and organic food. Method: Interviews using structured questionnaires were conducted twice with 115 city dwellers: when they started in the vegetable garden and about 6 months later. The questionnaire included questions related to environmental practices. The second evaluation also included questions related to the consumption of organic food, vegetables and fruit. Results: This research showed significant behavioural transformation, including positive outcomes in environmental practices such as recycling and trying to persuade friends or family to recycle, compost leftovers or choose to walk/bike to save petrol. In the opinion of the participants, activities in the organic community garden helped to increase consumption of fruits, vegetables and organic food. Conclusion: The study results reinforce the hypothesis that an organic community vegetable garden can induce significant, positive behavioural changes among its users. In particular this research suggests horticulture is associated with positive improvements in personal environmental behaviours, awareness of the environment's high social priority and increased consumption of organic food, fruit and vegetables. Resumen: Objetivo: Caracterizar las prácticas ambientales de los participantes de un jardín comunitario orgánico urbano al inicio de su experiencia en prácticas agrícolas y después de 6 meses, así como conocer su opinión sobre cómo esta actividad influyó en el consumo de verduras, frutas y alimentos orgánicos. Método: Las entrevistas con cuestionarios estructurados se realizaron dos veces a 115 habitantes de la ciudad: cuando comenzaron en la huerta y unos 6 meses después. El cuestionario incluyó preguntas relacionadas con las prácticas ambientales. La segunda evaluación incluyó también preguntas sobre el consumo de alimentos orgánicos, verduras y frutas. Resultados: Se observó una transformación conductual significativa, incluidos resultados positivos en prácticas ambientales como el reciclaje e intentar que amigos o familiares reciclen, la composta de sobras o elegir caminar o ir en bicicleta para ahorrar gasolina. En opinión de los participantes, las prácticas agrícolas de la comunidad orgánica contribuyeron a aumentar el consumo de frutas, verduras y alimentos orgánicos. Conclusión: Los resultados del estudio refuerzan la hipótesis de que un huerto comunitario orgánico puede inducir cambios conductuales significativos entre sus usuarios. En particular, esta investigación sugiere que la horticultura se asocia con mejoras positivas en los comportamientos ambientales y la conciencia de la alta prioridad social del medio ambiente y un mayor consumo de alimentos orgánicos, frutas y verduras. Keywords: Environment, Preventive medicine & public health, Community health, Organic agriculture, Organic food, Environmental health, Palabras clave: Medio ambiente, Medicina preventiva y salud pública, Salud comunitaria, Agricultura orgánica, Alimentos orgánicos, Salud ambiental